Pure Laparoscopic Augmentation Ileocystoplasty - Rafael B. Rebouças; Rodrigo C. Monteiro; Thiago N. S. de Souza; Augusto J. de Aragão; Camila R. T. Burity; Júlio C. de A. Nóbrega; Natália S. C. de Oliveira; Ramon B. Abrantes; Luiz B. Dantas Júnior; Ricardo Cartaxo Filho; Gustavo R. P. Negromonte; Rafael da C. R. Sampaio; et al. (International Brazilian Journal of Urology, 2014)
Introduction Guillain-Barre syndrome is an acute neuropathy that rarely compromises bladder function. Conservative management including clean intermittent catheterization and pharmacotherapy is the primary approach for hypocompliant contracted bladder. Surgical treatment may be used in refractory cases to improve bladder compliance and capacity in order to protect the upper urinary tract. We describe a case of pure laparoscopic augmentation ileocystoplasty in a patient affected by Guillain-Barre syndrome. Presentation A 15-year-old female, complaining of voiding dysfunction, recurrent urinary tract infection and worsening renal function for three months. A previous history of Guillain-Barre syndrome on childhood was related. A voiding cystourethrography showed a pine-cone bladder with moderate post-void residual urine. The urodynamic demonstrated a hypocompliant bladder and small bladder capacity (190mL) with high detrusor pressure (54 cmH2O). Nonsurgical treatments were attempted, however unsuccessfully. The patient was placed in the exaggerated Trendelenburg position. A four-port transperitoneal technique was used. A segment of ileum approximately 15-20cm was selected and divided with its pedicle. The ileal anastomosis and creation of ileal U-shaped plate were performed laparoscopically, without staplers. Bladder mobilization and longidutinal cystotomy were performed. Enterovesical anastomosis was done with continuous running suture. A suprapubic cystostomy was placed through a 5mm trocar. Results The total operative time was 335 min. The blood loss was minimal. The patient developed ileus in the early days, diet acceptance after the fourth day and was discharged on the seventh postoperative day. The urethral catheter was removed after 2 weeks. At 6-month follow-up, a cystogram showed a significant improvement in bladder capacity. The patient adhered well to clean intermittent self-catheterization and there was no report for febrile infections or worsening of renal function. We did not experience any complication related to the intestinal anastomosis fully prepared intracorporeally. Conclusions Albeit technically challenging, pure laparoscopic enterocystoplasty was feasible and safe. Preparing the enteral anastomosis and the pouch intracoporeally may prolong surgical time and contribute to postoperative ileus. Surgical staplers can assist in the procedure, however they are not essential.